Do contexto de resistência: intelectual e física - David Antonio da Costa; Diana Carvalho de Carvalho; Eliane Santana Dias Debus; Juliana Cristina Faggion Bergmann; Patricia Laura Torriglia (Universidade Federal de Santa Catarina, 2020)
.